2016
DOI: 10.1680/jgrim.15.00030
|View full text |Cite
|
Sign up to set email alerts
|

Field testing of permeation grouting using microfine cement

Abstract: Field tests are conducted on permeation grouting of ultra-microfine cement to examine whether zones of improved soil of a sufficient size can be created economically in sand deposits, which would be expected to contribute to improving ground conditions as a countermeasure against soil liquefaction. Four different tests are carried out under different grouting conditions, where grouting is conducted with and without forcible injection pressures, using cement solutions of different concentrations of (w/c) cs = 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Zebovitz et al [7], Karol [1] and Warner [8] stated that grouting could be performed easily for materials ranging from microfine cements to fine sands. Christodoulou et al [9], Markou and Droudakis [10], Hashimoto et al [11] observed that the strength of the sands increased after microfine cement was injected. Schwarz and Krizek [12] and Avci [13] suggested that the permeability coefficients of sands decreased after injecting microfine cement.…”
Section: Introductionmentioning
confidence: 99%
“…Zebovitz et al [7], Karol [1] and Warner [8] stated that grouting could be performed easily for materials ranging from microfine cements to fine sands. Christodoulou et al [9], Markou and Droudakis [10], Hashimoto et al [11] observed that the strength of the sands increased after microfine cement was injected. Schwarz and Krizek [12] and Avci [13] suggested that the permeability coefficients of sands decreased after injecting microfine cement.…”
Section: Introductionmentioning
confidence: 99%
“…Since the use of ultra microfine cement of the order of 1 m in particle diameter was found excellent in permeability as well as strength development, (Kanazawa 2012), permeation grouting using this newly developed micro-scaled cement agent has been examined continuously, (Hashimoto et al 2015(Hashimoto et al , 2016. From the experiences gained from the field tests conducted at the different two sites, this ground improvement technology was found to work well for relatively clean fine sand deposits, producing sizeable columns of improved soils.…”
Section: Introductionmentioning
confidence: 99%
“…Description of field trials to investigate permeation grouting of sands using ultra-micro-fine cement as a countermeasure against soil liquefaction is provided by Hashimoto et al (2016) in the sixth paper. Columns of improved soil of diameter 1·5-2 m and 2·5 m high were produced in a 3 m depth of relatively clean sand deposits, by introducing cement solutions with concentrations of (w/c) cs = 8 and 12 through boreholes set up along the entire depths of the sand deposits.…”
mentioning
confidence: 99%